Question
upstudy study bank question image url

37 On considère un nombre réel \( x \) tel que \( -3
Ask by Powers Chan. in Lebanon
Jan 13,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

**Encadrements des expressions pour \( -3 < x \leqslant 2 \):** a. \( -2 < x + 1 \leqslant 3 \) b. \( -4 < x - 1 \leqslant 1 \) c. \( -9 < 3x \leqslant 6 \) d. \( -10 \leqslant -5x < 15 \) e. \( -\frac{3}{2} < \frac{x}{2} \leqslant 1 \) f. \( -2 \leqslant -x < 3 \) g. \( -1 \leqslant -\frac{x}{2} < \frac{3}{2} \) h. \( -3 < 2x + 3 \leqslant 7 \)

Solution

Pour encadrer les expressions données en fonction de \( x \) tel que \( -3 < x \leqslant 2 \), nous allons déterminer les bornes inférieure et supérieure de chaque expression en appliquant les opérations nécessaires. Voici les encadrements pour chacune des expressions : ### a. \( x + 1 \) Ajoutons 1 aux inégalités de \( x \) : \[ -3 < x \leqslant 2 \\ \implies -3 + 1 < x + 1 \leqslant 2 + 1 \\ \implies -2 < x + 1 \leqslant 3 \] **Encadrement :** \[ -2 < x + 1 \leqslant 3 \] ### b. \( x - 1 \) Soustrayons 1 aux inégalités de \( x \) : \[ -3 < x \leqslant 2 \\ \implies -3 - 1 < x - 1 \leqslant 2 - 1 \\ \implies -4 < x - 1 \leqslant 1 \] **Encadrement :** \[ -4 < x - 1 \leqslant 1 \] ### c. \( 3x \) Multipliant par 3 (nombre positif, sens des inégalités inchangé) : \[ -3 < x \leqslant 2 \\ \implies 3 \times (-3) < 3x \leqslant 3 \times 2 \\ \implies -9 < 3x \leqslant 6 \] **Encadrement :** \[ -9 < 3x \leqslant 6 \] ### d. \( -5x \) Multipliant par -5 (nombre négatif, sens des inégalités inversé) : \[ -3 < x \leqslant 2 \\ \implies -5 \times 2 \leqslant -5x < -5 \times (-3) \\ \implies -10 \leqslant -5x < 15 \] **Encadrement :** \[ -10 \leqslant -5x < 15 \] ### e. \( \frac{x}{2} \) Divisant par 2 (nombre positif, sens des inégalités inchangé) : \[ -3 < x \leqslant 2 \\ \implies \frac{-3}{2} < \frac{x}{2} \leqslant \frac{2}{2} \\ \implies -\frac{3}{2} < \frac{x}{2} \leqslant 1 \] **Encadrement :** \[ -\frac{3}{2} < \frac{x}{2} \leqslant 1 \] ### f. \( -x \) Multipliant par -1 (nombre négatif, sens des inégalités inversé) : \[ -3 < x \leqslant 2 \\ \implies -2 \leqslant -x < 3 \] **Encadrement :** \[ -2 \leqslant -x < 3 \] ### g. \( -\frac{x}{2} \) Multipliant par \(-\frac{1}{2}\) (nombre négatif, sens des inégalités inversé) : \[ -3 < x \leqslant 2 \\ \implies -\frac{2}{1} \leqslant -\frac{x}{2} < \frac{3}{1} \implies -1 \leqslant -\frac{x}{2} < \frac{3}{2} \] **Encadrement :** \[ -1 \leqslant -\frac{x}{2} < \frac{3}{2} \] ### h. \( 2x + 3 \) Appliquons la transformation \( 2x + 3 \) aux inégalités de \( x \) : \[ -3 < x \leqslant 2 \\ \implies 2 \times (-3) + 3 < 2x + 3 \leqslant 2 \times 2 + 3 \\ \implies -6 + 3 < 2x + 3 \leqslant 4 + 3 \\ \implies -3 < 2x + 3 \leqslant 7 \] **Encadrement :** \[ -3 < 2x + 3 \leqslant 7 \] ### Récapitulatif des encadrements : \[ \begin{array}{ll} \text{a. } & -2 < x + 1 \leqslant 3 \\ \text{b. } & -4 < x - 1 \leqslant 1 \\ \text{c. } & -9 < 3x \leqslant 6 \\ \text{d. } & -10 \leqslant -5x < 15 \\ \text{e. } & -\frac{3}{2} < \frac{x}{2} \leqslant 1 \\ \text{f. } & -2 \leqslant -x < 3 \\ \text{g. } & -1 \leqslant -\frac{x}{2} < \frac{3}{2} \\ \text{h. } & -3 < 2x + 3 \leqslant 7 \\ \end{array} \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

Pour encadrer les expressions données en fonction de l'intervalle \( -3 < x \leqslant 2 \), nous allons utiliser les bornes de \( x \) pour calculer les bornes des expressions. **a. \( x+1 \)** Pour \( x = -3 \) : \( -3 + 1 = -2 \) (non inclus) Pour \( x = 2 \) : \( 2 + 1 = 3 \) Donc, \( -2 < x + 1 \leq 3 \). **b. \( x-1 \)** Pour \( x = -3 \) : \( -3 - 1 = -4 \) Pour \( x = 2 \) : \( 2 - 1 = 1 \) Donc, \( -4 < x - 1 \leq 1 \). **c. \( 3x \)** Pour \( x = -3 \) : \( 3 \times (-3) = -9 \) Pour \( x = 2 \) : \( 3 \times 2 = 6 \) Donc, \( -9 < 3x \leq 6 \). **d. \( -5x \)** Pour \( x = -3 \) : \( -5 \times (-3) = 15 \) Pour \( x = 2 \) : \( -5 \times 2 = -10 \) Donc, \( -10 \leq -5x < 15 \). **e. \( \frac{x}{2} \)** Pour \( x = -3 \) : \( \frac{-3}{2} = -1.5 \) Pour \( x = 2 \) : \( \frac{2}{2} = 1 \) Donc, \( -1.5 < \frac{x}{2} \leq 1 \). **f. \( -x \)** Pour \( x = -3 \) : \( -(-3) = 3 \) Pour \( x = 2 \) : \( -2 \) Donc, \( -2 \leq -x < 3 \). **g. \( -\frac{x}{2} \)** Pour \( x = -3 \) : \( -\frac{-3}{2} = 1.5 \) Pour \( x = 2 \) : \( -\frac{2}{2} = -1 \) Donc, \( -1 < -\frac{x}{2} \leq 1.5 \). **h. \( 2x + 3 \)** Pour \( x = -3 \) : \( 2 \times (-3) + 3 = -6 + 3 = -3 \) Pour \( x = 2 \) : \( 2 \times 2 + 3 = 4 + 3 = 7 \) Donc, \( -3 < 2x + 3 \leq 7 \). Voici l'encadrement des expressions : \( \begin{array}{lll} \text{a.} & -2 < x + 1 \leq 3 \\ \text{b.} & -4 < x - 1 \leq 1 \\ \text{c.} & -9 < 3x \leq 6 \\ \text{d.} & -10 \leq -5x < 15 \\ \text{e.} & -1.5 < \frac{x}{2} \leq 1 \\ \text{f.} & -2 \leq -x < 3 \\ \text{g.} & -1 < -\frac{x}{2} \leq 1.5 \\ \text{h.} & -3 < 2x + 3 \leq 7 \\ \end{array} \)

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy